Ameliorating effect of chotosan and its active component, Uncaria hook, on lipopolysaccharide-induced anxiety-like behavior in mice - Okawa, Yasumasa; Ushio, Soichiro; Izushi, Yasuhisa; Kitamura, Yoshihisa; Zamami, Yoshito; Sendo, Toshiaki (Frontiers in Pharmacology, 2024)
In this study, we aimed to examine the effects of chotosan, a traditional Japanese botanical drug, and its active component, Uncaria hook, on anxiety-like behaviors induced by systemic inflammation in mice.To induce systemic inflammation, the mice were treated with lipopolysaccharide (LPS), a bacterial endotoxin. Prior to LPS treatment, the mice were administered chotosan or Uncaria hook orally each day for 14 days. Anxiety-like behavior of the mice was evaluated using the light-dark test 24 h after LPS treatment.Results: Repeated administration of chotosan prevented anxiety-like behavior in both normal and LPS-treated mice. Similarly, administration of Uncaria hook suppressed LPS-induced anxiety-like behavior in mice. Furthermore, treatment with tandospirone, a 5-HT1A receptor agonist, alleviated anxiety-like behavior in mice, whereas treatment with DOI, a 5-HT2A receptor agonist, enhanced anxiety-like behavior in mice. LPS treatment significantly increased serotonin (5-HT)2A receptor mRNA expression in the frontal cortex, whereas 5-HT1A receptor mRNA expression remained unchanged in the hippocampus. Notably, chotosan significantly suppressed the mRNA expression of 5-HT2A receptor.Discussion: These findings indicate that chotosan exerts anxiolytic-like effects in the context of inflammation-induced anxiety, potentially mediated by the inhibition of 5-HT2A receptor hyperfunction in LPS-treated mice. Consequently, we postulate that chotosan may be effective in managing inflammation-induced anxiety-like behaviors.